The content of the total protein, protein fractions and blood serum proteins in patients with different forms of lichen ruber planus - Barannik, N. G.; Tsymbaliuk, R. Y.; Manukhina, O. M.; Sydoryako, A. V.; Volchykhina, K. P. (Modern medical technology, 2021)
Purpose of the study. Establishing the role of processes of proteolysis of mixed saliva in the development and course of lichen planus of the oral mucosa. Materials and methods. A comprehensive examination of 102 patients with lichen planus aged 21 to 70 years and 20 people in the control group, whose age and sex composition corresponded to that in the study group. BioRad (USA) reagent kits were used to determine the total protein content of mixed saliva. The content of protein fractions of mixed saliva was determined by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate. Determination of serum proteins in mixed saliva was performed by quantitative (cross) immunoelectrophoresis. Results. In patients with lichen planus, the overall proteolytic activity of mixed saliva increases with a significant increase in the concentration of α1proteinase inhibitor, especially in exudative hyperemic and erosiveulcerative forms of the disease. Diffusion of α1proteinase inhibitor into mixed saliva increases its antiproteolytic potential and has a protective character. The content of albumin and ceruloplasmin in the mixed saliva of patients with lichen planus increases depending on the severity of the disease: typical, hyperkeratotic, exudativehyperemic, erosiveulcerative. Conclusions. Mixed saliva of patients with lichen planus in contrast to patients in the control group is characterized by the predominance of low molecular weight proteins (20–79 kDa) over high molecular weight. The level of albumin, α1proteinase inhibitor and ceruloplasmin in the mixed saliva of patients with lichen planus increases and correlates with the severity of the disease. The content of IgA in the mixed saliva of patients with lichen planus increases, depending on the form of the disease.